Electromagnetic loss mechanisms in antimony doped tin oxide and reduced graphene oxide multilayer films. Issue 7 (May 2020) - Huang, Xiaogu; Zhang, Yunke; Li, Xiaolong; Zhang, Mingji
Abstract: In this paper, the antimony doped tin oxide (ATO) and reduced graphene oxide (rGO) were prepared by coprecipitation method and modified Hummers' method, respectively. Both were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and vector network analyzer (VNA). The as-prepared rGO showed typical sheets-like structure and the as-prepared ATO showed typical nano-particle shape. Then, the ATO and rGO multilayer films were designed and the microwave absorption performances were numerically evaluated using finite element methods. The results showed that synergetic effects of interfacial polarization resonance and 1/4λ elimination were stimulated in 10-layerd 1.8 mm multilayer films to give a minimal reflection loss of −45.2 dB @ 16.1 GHz, and −10 dB bandwidth of 5.4 GHz, which was enhanced more than −30 dB in ATO or rGO monophase absorbers with the same thickness. This work provides a novel technical route to realize high-performance microwave absorbers in terms of simultaneously stronger absorption, broader absorption bandwidth and smaller thickness to facilitate higher flexibility and stability for practical applications.